Role of Dolutegravir/Lamivudine in the Management of Pregnant People Living with HIV-1: A Narrative Review - William R. Short; Parul Patel; Gustavo Verdier; Ana Puga; Vani Vannappagari; Annemiek de Ruiter; Bryn Jones (Infectious Diseases and Therapy)
Abstract Lowering viral load during pregnancy is regarded as the most important method of reducing human immunodeficiency virus 1 (HIV-1) vertical transmission risk, and minimizing fetal exposure to drugs is a guiding principle during pregnancy. Dolutegravir/lamivudine (DTG/3TC) has demonstrated high efficacy, a high barrier to resistance, and a good safety profile in non-pregnant individuals; however, DTG/3TC is not recommended by perinatal HIV treatment guidelines for initial therapy in pregnant people living with HIV-1 because of limited data on use of the 2-drug regimen during pregnancy. Efficacy and pharmacokinetic data from pregnant individuals using DTG and/or 3TC are reviewed and used to extrapolate anticipated DTG/3TC efficacy in pregnancy. There are robust data on the use of DTG- and 3TC-containing combination regimens, which are recommended by perinatal HIV treatment guidelines during pregnancy, supporting their well-established efficacy and safety in pregnant people living with HIV-1. Updated data from the Tsepamo and Eswatini surveillance studies (> 14,000 DTG exposures from conception) indicate no increased risk of neural tube defects with DTG. Pharmacokinetic data for DTG and 3TC indicate that exposures in pregnancy are within the therapeutically effective range seen in non-pregnant adults. Two studies evaluated DTG/3TC during pregnancy and both reported high virologic suppression rates [HIV-1 ribonucleic acid (RNA) < 50 copies/mL at delivery: 97% (30/31) overall], no events of vertical transmission, and no new safety signals, consistent with the use of DTG-based 3-drug regimens in pregnancy. The use of DTG/3TC during pregnancy is anticipated to be comparably effective and well tolerated for both parental health and prevention of vertical transmission with fetal exposure to fewer antiretrovirals compared with 3- or 4-drug regimens. These considerations are relevant when evaluating use of DTG/3TC in people living with HIV-1 who are pregnant or considering pregnancy in clinical practice and in perinatal HIV treatment guidelines. Video abstract available for this article. Supplementary file1 (MP4 319,147 KB)